2018
DOI: 10.1002/jhet.3329
|View full text |Cite
|
Sign up to set email alerts
|

Isatin–Coumarin Hybrids Tethered via Diethylene Glycol: Design, Synthesis, and Their In Vitro Antitumor Activities

Abstract: A series of novel isatin–coumarin hybrids was designed, synthesized, and assessed for their in vitro antitumor activities against drug‐sensitive HepG2, Hela, A549, DU145 (prostatic cancer), SKOV3, and MCF‐7 as well as drug‐resistant MCF‐7/DOX (doxorubicin‐resistant MCF‐7) human cancer cell lines. Results revealed that the synthesized hybrids displayed considerable activities against the tested seven cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A novel series of twelve ethylene glycol-tethered coumarin–isatin hybrids were designed and evaluated for their in vitro anticancer activities against HepG2, HeLa, A549, DU145, SKOV3, and MCF-7, and drug-resistant MCF-7/DOX (doxorubicin-resistant MCF7) by SRB assay. 148 Among them, compound 84a showed the maximum potency against HepG2, A549, DU145, MCF-7, and MCF-7/DOX with IC 50 values of 10.28, 10.92, 20.80, 11.29, and 14.45 μM, respectively. Compounds 84b and 84c possessed the highest efficiency against the HeLa and SKOV3 cell lines with IC 50 values of 11.54 and 18.63 μM, respectively ( Fig.…”
Section: Coumarin Hybridsmentioning
confidence: 96%
See 1 more Smart Citation
“…A novel series of twelve ethylene glycol-tethered coumarin–isatin hybrids were designed and evaluated for their in vitro anticancer activities against HepG2, HeLa, A549, DU145, SKOV3, and MCF-7, and drug-resistant MCF-7/DOX (doxorubicin-resistant MCF7) by SRB assay. 148 Among them, compound 84a showed the maximum potency against HepG2, A549, DU145, MCF-7, and MCF-7/DOX with IC 50 values of 10.28, 10.92, 20.80, 11.29, and 14.45 μM, respectively. Compounds 84b and 84c possessed the highest efficiency against the HeLa and SKOV3 cell lines with IC 50 values of 11.54 and 18.63 μM, respectively ( Fig.…”
Section: Coumarin Hybridsmentioning
confidence: 96%
“…In 2015, some triazole-modified coumarin-based compounds (148) were patented, which were proposed to be used in the treatment of various cancers such as breast and prostate cancer. 242 The general structure of the compounds is shown in Fig.…”
Section: Patentsmentioning
confidence: 99%
“…The structure–activity relationship suggested that the substitution of fluorine at the fifth position of isatin was beneficial for the activity of the compound, while the replacement with a chlorine atom decreased the activity of the compound. The introduction of a NOH group at the third position of the isatin led to a decrease in activity [ 82 ]. Similarly, Xu et al introduced a glycol fragment and synthesized glycol-tethered isatin–coumarin hybrids, which were evaluated for anticancer activity against breast cancer cell lines.…”
Section: Synthetic Coumarin-inspired Derivatives With Anti-breast Can...mentioning
confidence: 99%
“…The majority of coumarin–isatin hybrids 5 (IC 50 : 10.28–49.97 μM, SRB assay) with 1,2,3‐triazole moiety compared with hybrids 4 were active against HepG2, HeLa, A549, DU145, SKOV3, MCF‐7, and doxorubicin‐resistant MCF‐7 cancer cell lines, suggesting the 1,2,3‐triazole moiety was harmful to the activity. [ 34,36 ] The SAR proved that the length of the linker influenced the activity remarkably and the extension of the linker decreased the activity. [ 36,37 ] Introduction of oxime into the C‐3 position and the halogen atom into the C‐5 position of isatin skeleton could boost up the activity and the most active hybrid 5a (IC 50 : 10.28–27.36 μM, SRB assay) was not inferior to etoposide (IC 50 : 6.94–31.79 μM) against HepG2, DU145, SKOV3, and MCF‐7 cancer cell lines, and >2.8‐fold more potent than etoposide (IC 50 : >50 μM) against HeLa, A549 and doxorubicin‐resistant MCF‐7 cancer cell lines.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%
“…[ 34,36 ] The SAR proved that the length of the linker influenced the activity remarkably and the extension of the linker decreased the activity. [ 36,37 ] Introduction of oxime into the C‐3 position and the halogen atom into the C‐5 position of isatin skeleton could boost up the activity and the most active hybrid 5a (IC 50 : 10.28–27.36 μM, SRB assay) was not inferior to etoposide (IC 50 : 6.94–31.79 μM) against HepG2, DU145, SKOV3, and MCF‐7 cancer cell lines, and >2.8‐fold more potent than etoposide (IC 50 : >50 μM) against HeLa, A549 and doxorubicin‐resistant MCF‐7 cancer cell lines. Thus, hybrid 5a might be a promising compound for the development of new chemotherapy anticancer agents in the future.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%